2022
DOI: 10.3390/epigenomes6020013
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Cardiovascular Defects and Cardiac Epigenome in the Context of COVID-19

Abstract: Although few in number, studies on epigenome of the heart of COVID-19 patients show that epigenetic signatures such as DNA methylation are significantly altered, leading to changes in expression of several genes. It contributes to pathogenic cardiac phenotypes of COVID-19, e.g., low heart rate, myocardial edema, and myofibrillar disarray. DNA methylation studies reveal changes which likely contribute to cardiac disease through unknown mechanisms. The incidence of severe COVID-19 disease, including hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 194 publications
(232 reference statements)
0
2
0
Order By: Relevance
“…This revealed differentially methylated sites in the heart (172 sites) and kidney (49 sites), suggesting that tissue-specific epigenetic changes occur soon after SARS-CoV-2 infection [13]. Other studies have also reported the adverse effects of COVID-19 on the heart [14]. These findings help us to better understand COVID-19's disease presentation, suggesting that SARS-CoV-2 induces metabolic reprogramming and epigenetic changes, which may contribute to systemic toxicity.…”
Section: Sars-cov-2 Induces Metabolic Reprogramming and Epigenetic Ch...mentioning
confidence: 91%
“…This revealed differentially methylated sites in the heart (172 sites) and kidney (49 sites), suggesting that tissue-specific epigenetic changes occur soon after SARS-CoV-2 infection [13]. Other studies have also reported the adverse effects of COVID-19 on the heart [14]. These findings help us to better understand COVID-19's disease presentation, suggesting that SARS-CoV-2 induces metabolic reprogramming and epigenetic changes, which may contribute to systemic toxicity.…”
Section: Sars-cov-2 Induces Metabolic Reprogramming and Epigenetic Ch...mentioning
confidence: 91%
“…Kelsey Dawes et al explore epigenetic analyses of alcohol consumption in combustible and non-combustible nicotine product users in a biochemically verified cohort of exclusive cigarette smokers [ 5 ]. Shreya Sarkar et al present the current scenario of cardiovascular diseases and congenital heart defects associated with COVID-19 patients and provide a developmental biology perspective of the roles of angiotensin-converting enzyme 2 (ACE2) and its axis members [ 6 ].…”
mentioning
confidence: 99%